2017
DOI: 10.5603/njo.2017.0039
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells and their clinical significance

Abstract: Metastases to other organs and the formation of secondary tumors are responsible for 90% of cancer-related deaths. However, even in the early stages of cancer, about 30-40% of patients with localized disease may have latent metastasis, which are likely derived from circulating tumor cells (CTCs) involved in disease progression. Therefore, detection and analysis of CTCs can play an important role in the diagnosis and decision-making of adjuvant treatment that aims to prevent metastasis. At present, patients' se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…We found that the HMGA1 expression in the blood tends to decrease after surgical removal of the NSCLC tumor that could suggest tumor cells are the substantial source of HMGA1 expression measured in the blood. It is believed that circulating tumor cells are shredded into the circulation by tumors in the early stages of cancer and are responsible for the development of latent metastases (Grzybowska and Fabisiewicz 2017 ). However, according to the Human Protein Atlas (Uhlen et al 2017 ) the HMGA1 expression was detected in all blood cell types, so the type of cells being the source of measured HMGA1 transcript level should be specified in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the HMGA1 expression in the blood tends to decrease after surgical removal of the NSCLC tumor that could suggest tumor cells are the substantial source of HMGA1 expression measured in the blood. It is believed that circulating tumor cells are shredded into the circulation by tumors in the early stages of cancer and are responsible for the development of latent metastases (Grzybowska and Fabisiewicz 2017 ). However, according to the Human Protein Atlas (Uhlen et al 2017 ) the HMGA1 expression was detected in all blood cell types, so the type of cells being the source of measured HMGA1 transcript level should be specified in the future.…”
Section: Discussionmentioning
confidence: 99%